Correlation of Vascular Patterns in Skin Lesions With LC-OCT and Dermoscopy With a Tridimensional Perspective: A Pilot Study - Clément Lenoir; Mariano Suppa; Susana Puig; Véronique del Marmol; Raquel Albero; Llucia Also; Carmen Orte Cano; Gwendoline Diet; Margot Fontaine; Linda Tognetti; Elisa Cinotti; Pietro Rubegni; et al. (Dermatology Practical & Conceptual)
Introduction: Vascular patterns play a crucial role in the diagnosis and differentiation of skin lesions by providing insight into underlying pathology and aid in distinguishing between benign and malignant lesions. While dermoscopy has proven valuable for visualizing these vascular structures, Line-field confocal optical coherence tomography (LC-OCT) offers high-resolution, 3-dimensional (3D) imaging of the skin, potentially providing detailed visualization of vascular architecture and new insights about their projection in dermoscopy.